Angiotensin II receptor blocker attenuates stress pressor response in young adult African Americans. Issue 8 (22nd July 2019) - Jeong, Jin Hee; Hanevold, Coral; Harris, Ryan A.; Kapuku, Gaston; Pollock, Jennifer; Pollock, David; Harshfield, Gregory
Abstract: African Americans (AAs) are susceptible to hypertension (HTN) and its associated organ damage leading to adverse cardiovascular (CV) outcomes. Psychological stress is proposed to contribute to the development of HTN; however, the potential role of the renin‐angiotensin system (RAS) in stress‐related HTN in AAs is largely unknown. In this study, we tested the hypothesis that activation of RAS is a potential contributing factor for altered CV responses to stress, and suppression of angiotensin II (Ang II) activity will improve hemodynamic responses to a prolonged mental stressor in healthy young AAs. Utilizing a double‐blind, randomized, crossover study design, 132 normotensive AAs (25 ± 7 years) were treated with either a placebo (PLC) or 150 mg/d irbesartan (an Ang II type 1 receptor blocker; ARB) for 1 week. On the final day of each treatment, hemodynamic measures and urinary sodium excretion (UNaV) were collected before, during and after a 45 minute‐mental stress. The magnitude of stress‐induced increase in blood pressure with ARB was blunted and delayed compared to PLC. Systolic blood pressure at the end of recovery on ARB was significantly lower compared to either PLC (110 ± 13 vs 117 ± 12 mm Hg respectively; P  < 0.001) or the prestress level on ARB ( P  = 0.02). ARB treatment reduced overall vasoconstriction and improved poststress UNaV. ARB attenuated blood pressure responses to mental stress and improved the poststress BP recovery process which were partly linked to reduced overall vasoconstriction and improved stress‐induced UNaV in young adult AAs prior to the development of disease conditions. These results suggest that treatment approaches that inhibit RAS action could have significant relevance to potentially lower susceptibility to stress responses and eventually the premature development of HTN in AAs.